Bentuk Pertanggungjawaban Indonesia Dalam Pencemaran Udara Lintas Batas Negara - Veri Mei Hafnizal (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2018)
Indonesia’s inability to solve the problem of forest fires does not mean that Indonesia is a passive country in protecting the environment. This research is conducted through normative juridical research method or library research. Principle 21 of the Stockholm Declaration (United Men’s Resolution 2992 (XXVII)of December 15, 1972) mention that each country has sovereign right to exploit its natural resources and responsible for any exploitation activities within its territory or under its control, it does not cause harm or damage to other countries. The principle of state accountability as one of the main principles in international law essentially contains the obligation of the state which gives impact to other countries to make reparation to the disadvantaged activities and return the condition of the country as originally. International law in this current time, it should be maintained its existence as one of alternative disputesettlement at international level. The existence of the principle of state responsibility on the hard law level should be given priority as one of the efforts of the realization of equality before the law at international level.